The combined impacts of toxic drug use and the 2021 Heat Dome in Canada: A thematic analysis of online news media articles - Emily J. Tetzlaff; Nicholas Goulet; Melissa Gorman; Glen P. Kenny (PLoS ONE, 2025)
Introduction During the summer of 2021, western Canada experienced a historic and deadly extreme heat event. Simultaneously, toxic drug use and overdoses related to high-risk use of opioids and polysubstance use continued to rise across the country. However, the combined impacts of these intersecting public health crises remain poorly understood as relevant data sources are limited in Canada. Methods We explored news media articles (n = 86, 3%) discussing toxic drug use, overdose-related deaths and the 2021 Heat Dome which were identified in a systematic review of Canadian online news media (e.g., newspaper articles, radio broadcasts) from five subscription news databases and an extensive grey literature search (n = 2909). The analyzed articles were published before, during and after the 2021 Heat Dome, and were qualitatively coded and thematically analyzed in NVivo to identify patterns of meaning across the dataset. Results Four main themes were identified within our media-based analysis: (I) the reported impact of toxic drug use on human thermoregulation and behavioural adaptation; (II) the reported demand of intersecting crises on the health system; (III) barriers and stigma reported to influence an individual’s access to or use of heat mitigation behaviours and services; and (IV) the reported impact of extreme heat on the public health response to drug poisoning emergencies. Conclusion With increasing temperature extremes and a rising tide of toxic drug use and overdoses, our findings illustrate that there is a need for further research to better understand the combined impacts when toxic drug use, overdose-related deaths, and extreme heat coincide.